The dynamics of purposeful change: a model - Howard Silverman; Gregory M. Hill (Ecology and Society, 2018)
In order to describe and depict the dynamics of purposeful change, we reexamine the concept of social-ecological systems (SES) and propose a linked but not integrated SES model. Adapting core resilience tools (stability landscape and panarchy), we construct a general model and then use a framework of key concepts (identity, logics, affiliations, affordances) to analyze the dynamics depicted therein. We illustrate this model's use in two cases: a retrospective analysis of food-systems work amidst contending social regimes and an interpretive reading of published narratives describing individual-to-ecological stability and change. We discuss this model's applicability in situations involving divergent perspectives, micro-meso-macro social dynamics, social regime identity, and the distinct dynamics of social and ecological systems. This examination illustrates the power and flexibility of these core resilience tools.